Image-Based Sexual Abuse: An Australian Reflection - Flynn, Asher (Women & criminal justice, 2021)
Digital technologies are increasingly being used to abuse, harass, and victimize women. Image-based sexual abuse (IBSA)—the nonconsensual taking or sharing (including threats to share) nude or sexual images—is one such form of abuse. Various jurisdictions have enacted laws criminalizing IBSA, but Australia is arguably leading the way, with eight of its nine jurisdictions introducing innovative IBSA laws. This article explores the Australian laws, focusing on their capacity to address the gendered nature of IBSA. While highlighting the importance of these laws, we argue that a multifaceted approach is required to combat IBSA that includes law reform, education, and training.